ALK-Rearranged Renal Cell Carcinoma: A Case Report with Review of Literature - Deshpande, Gauri; Arora, Amandeep; Katdare, Aparna; Prakash, Gagan; Joshi, Amit; Murthy, Vedang; Desai, Sangeeta; Menon, Santosh (Indian Journal of Medical and Paediatric Oncology, 2025)
Anaplastic lymphoma kinase (ALK) rearranged renal cell carcinoma (RCC) is a newly recognized entity in the 2022 WHO classification under molecularly defined renal tumors. It is imperative to diagnose this entity, especially with the advent of ALK-directed therapy. Herein, we report the case of a 52-year-old lady who presented with incidentally detected mass in the mid-pole of the left kidney. The patient underwent left radical nephrectomy. Microscopically, the tumor showed varied patterns, namely, papillary, tubulocystic, solid, and varied cell morphologies—cuboidal cells with low-grade nuclei, and rhabdoid cells in nests and clusters. Locoregional spread to the lymph nodes was noted. The tumor was reported as “renal cell carcinoma, unclassified.” On further immunohistochemistry, the tumor was diffusely positive for ALK by immunohistochemistry. Further, the finding of ALK rearrangement was confirmed by fluorescence in situ hybridization, thus confirming the diagnosis of ALK-rearranged RCC. She came back with progression after a year and was started on ALK-directed therapy after confirmation of ALK rearrangement. However, she succumbed to the disease 15 months after diagnosis. ALK-directed therapy has revolutionized the management of ALK-positive lung adenocarcinomas. Although ALK-rearranged RCC is a rare subtype of RCC, it is essential to know this case histopathologically for an accurate diagnosis and future development of targeted therapy.
Keywords: ALK-rearranged renal cell carcinoma; histopathology; fluorescence in-situ; hybridization